Development of a Microcontroller E-Module Based on Grove Beginner Kit for Arduino Informatics Subject - Ariza, Rojian; Nirawana, I Wayan Sugianta; Rusdiana, Rusdiana (UNDIKMA, 2025)
Lack of teaching materials, time limitations, and uninteresting materials are problems that need to be solved so that students can better understand learning at school. The researcher provides solutions to develop E-modules that can be accessed on the internet. This research aims to develop E-module based on a microcontroller based on the Grove Beginner Kit for Arduino as a teaching material for informatics subjects and to determine the feasibility of e-modules in Arduino microcontroller material class XI at SMA Negeri 10 Samarinda. This type of research is development using a 4-D model, consisting of Define, Design, Develop, and Disseminate. Studies show that the results of E-module tests by material experts result in an average percentage of 90%, with a very decent category. The average percentage of media expert assessments is 92%, and the E-modules are feasible to implement. Overall, the combined average of the due diligence by experts reached 91%, with the category of very feasible. The results of student responses were obtained with an average percentage of 81% with very feasible criteria. so it can be concluded that the Grove Beginner Kit-based microcontroller e-module for Arduino can be applied or disseminated at SMA Negeri 10 Samarinda. Further research is expected to be carried out on other development models such as the borg and gaal models or the R2D2 model (reflective, recursive design and development).Â .